Analisis Kemampuan Siswa Dalam Membaca Permulaan - Bidariyah, Ilham; Husaen Suderajat; Wawan Samudera (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
Pre-reading is the initial stage of learning to read given in grades I and II and an activity where students begin learning activities by introducing letters through word symbols.. Of the 28 children, there are 7 students who cannot read, because the average child does not enter Early Childhood Education and lacks supervision from parents. The aim is to determine the reading ability at the beginning of class II MI Attarbiyah Addiniyah. The type of research used in this research is quantitative research with descriptive methods. The results of the research concluded that the initial reading ability in Class II MI Attarbiyah Addiniyah Gersik Kediri was very good with an average score of 81.94, this assessment was included in the Minimum Completeness Criteria (KKM). Because the Minimum Completeness Criteria (KKM) value is 70%, of the 28 students there are 7 who experience problems in their abilities. From the results of the research and discussion it can be concluded that "Analysis of Students' Ability to Read Beginning Class II MI Attarbiyah Addiniyah Gersik Kediri Academic Year 2022/2023". We can see from the results of the average student score, namely 81.94%.